2010
DOI: 10.1016/j.corsci.2009.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen induced cracking (HIC) testing of low alloy steel in sour environment: Impact of time of exposure on the extent of damage

Abstract: The selection of materials for application in the oil and gas industry in environments containing hydrogen sulphide (H 2 S) is an important matter for the safety of equipments. In the presence of H 2 S, hydrogen atoms originating from the cathodic corrosion reaction can diffuse into the steel, resulting in cracking mechanisms such as hydrogen-induced cracking (HIC) or sulphide stress cracking (SSC). For the SSC cracking mode, a diagram defining different regions of environmental severity was established in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 26 publications
(14 reference statements)
5
33
0
2
Order By: Relevance
“…Sosa [6], Cabrera-Sierra [7], Kittel [8], Hernández-Espejel [9] and Zhou [10] reported that the protective property of the sulphide film depended on the factors such as the H 2 S partial pressure (PH 2 S), temperature and pH. The sulphide layer performed better protective property in the acid solution than that in the neutral solution under 1 bar H 2 S at ambient temperature [8,11]. However, Tang [12] and Kim [13] reported that the corrosion rate and the hydrogen permeation rate of carbon steel increased with decreasing pH values of the solution under 1 bar H 2 S because the solubility of sulphide increased with decreasing pH value.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sosa [6], Cabrera-Sierra [7], Kittel [8], Hernández-Espejel [9] and Zhou [10] reported that the protective property of the sulphide film depended on the factors such as the H 2 S partial pressure (PH 2 S), temperature and pH. The sulphide layer performed better protective property in the acid solution than that in the neutral solution under 1 bar H 2 S at ambient temperature [8,11]. However, Tang [12] and Kim [13] reported that the corrosion rate and the hydrogen permeation rate of carbon steel increased with decreasing pH values of the solution under 1 bar H 2 S because the solubility of sulphide increased with decreasing pH value.…”
Section: Introductionmentioning
confidence: 98%
“…The corrosion scale acted as a diffusion barrier for the species involved in the corrosion process can slow down the corrosion process and prevent the underlying steel from further dissolution [5]. Sosa [6], Cabrera-Sierra [7], Kittel [8], Hernández-Espejel [9] and Zhou [10] reported that the protective property of the sulphide film depended on the factors such as the H 2 S partial pressure (PH 2 S), temperature and pH. The sulphide layer performed better protective property in the acid solution than that in the neutral solution under 1 bar H 2 S at ambient temperature [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that hydrogen atoms produced due to surface corrosion of the steel diffuse into it through microstructural defects that exist in the material [38]. The accumulation of a critical amount of hydrogen in the metal defeats results in HIC initiation and propagation, as recently reported by Kittel et al [39].…”
Section: Surface Characterizationsmentioning
confidence: 59%
“…These fractures can be the beginning of more serious damage for the integrity of API 5L X52 steel, when exposed to environments with high hydrogen sulfide contents. Under these conditions, the development of some characteristic corrosion processes such as hydrogen induced cracking (HIC), sulfide stress cracking (SSC) and stress-oriented-hydrogen-induced cracking (SOHIC) [32] [33] [34] has been observed. In this particular case and according to what has been established by some researchers, this corrosion type would seem to be the most common failure for the steel, being the most dangerous mechanism for a metal fracture, as it can occur instantaneously without previous warning [21].…”
Section: Discussionmentioning
confidence: 99%